Prodi's government: First steps at home and abroad - Ruth Hanau Santini (Stiftung Wissenschaft und Politik (SWP), 2006)
After five years of political marginality within the EU, and few international benefits from divisive foreign policy choices, Italy after Silvio Berlusconi seems eager to restore its traditionally pro-European stance, starting with its withdrawal from Iraq. While Romano Prodi's credentials in this respect leave no room for misinterpretation, what loom on the not so distant horizon are the country's economic challenges. The question is whether the left-wing coalition, headed by the former President of the European Commission, will be able to deliver, and what should be realistically expected from it. (SWP Comments / SWP)
Keywords: 320